2020
DOI: 10.1155/2020/4340521
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of a CT-Based Radiomic Signature for Preoperative Prediction of Early Recurrence in Hypopharyngeal Carcinoma

Abstract: Purpose. In the clinical management of hypopharyngeal squamous cell carcinoma (HSCC), preoperative identification of early recurrence (≤2 years) after curative resection is essential. Thus, we aimed to develop a CT-based radiomic signature to predict early recurrence in HSCC patients preoperatively. Methods. In total, 167 HSCC patients who underwent partial surgery were enrolled in this retrospective study and divided into two groups, i.e., the training cohort (n=133) and the validation cohort (n=34). Each ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that radiomics in computed tomography (CT) imaging can improve the prediction of prognosis of HNSCC . Radiomics on CT HNSCC imaging has been used to predict HPV status [8,9], overall survival [10][11][12][13][14], progression-free survival [10,[12][13][14], local tumour control [8,12,[15][16][17][18][19][20][21], tumour grade [9,22], lymph node response [23,24], tumour invasiveness [9,25], xerostomia [26][27][28], tumour resectability [29], and classifying molecular subtypes [30,31]. While the survival studies show that radiomics on CT data can significantly stratify patients in multiple survival groups, performance expressed through Harrell's C index ranged widely, from 0.58 to 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that radiomics in computed tomography (CT) imaging can improve the prediction of prognosis of HNSCC . Radiomics on CT HNSCC imaging has been used to predict HPV status [8,9], overall survival [10][11][12][13][14], progression-free survival [10,[12][13][14], local tumour control [8,12,[15][16][17][18][19][20][21], tumour grade [9,22], lymph node response [23,24], tumour invasiveness [9,25], xerostomia [26][27][28], tumour resectability [29], and classifying molecular subtypes [30,31]. While the survival studies show that radiomics on CT data can significantly stratify patients in multiple survival groups, performance expressed through Harrell's C index ranged widely, from 0.58 to 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies, all of them retrospective, were subjected to qualitative analysis [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The demographic characteristics of patients from these studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that wavelet-LHL_firstorder_Maximum and wavelet-LHL-firstorder_Kurtosis—two features extracted from post-contrast CT images—successfully predicted PFS in patients with locally advanced hypopharyngeal cancer who had undergone induction chemotherapy [ 23 ]. Finally, Li et al [ 24 ] developed a CT radiomic signature based on first-order features (i.e., minimum, skewness, and total energy) to be used in the preoperative phase for predicting early recurrences of hypopharyngeal cancer. Second-order radiomic features—also termed texture features—reflect the statistical relationships of gray levels within an image and represent a proxy for intratumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%